Influence of employer brand traits on workplace preference - Czinczel, Milena (2024)
In today's competitive talent market, employer branding is crucial for consulting firms like McKinsey & Company. As graduates in 2024 increasingly prioritize work-life balance, job security, and supportive culture, this research examines the key employer brand traits that attract top talent to McKinsey. Throught in-depth interviews, the study reveals specific factors in McKinsey’s employer brand that attract top talent, providing valuable managerial implications to enhance the firm's recruitment and employer branding strategies.